Lithium cobalt oxide positive electrode material matched with silicon-carbon negative electrode and preparation method of lithium cobalt oxide positive electrode material
By forming a nano-clad layer of 0 to 20 nm on the lithium cobalt oxide positive electrode material, the SEI film growth and Li ion consumption problems caused by silicon carbon negative electrode material in lithium-ion batteries are solved, and the battery performance with high energy density and long cycle life is achieved.
Patent Information
- Application Number
- CN202411891909.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
AI Technical Summary
In lithium-ion batteries, the volume expansion of silicon carbon anode material during charging and discharging, resulting in the continuous growth of solid electrolyte membrane (SEI), consumes Li ions, and reduces battery capacity and cycle stability.
The lithium cobalt oxide positive electrode material is used, and the outermost surface of the 0-20nm cladding layer is xLi2Mn1-zM1zO(3-y)Fy·(1-x)Li2M1aOb is prepared by wet mixing, nanomilling and calcining to form a nanostructure and cladding layer, stabilize the SEI film and improve the lithium ion transmission rate.
High energy density and long cycle life are achieved, and the cycle stability and capacity retention rate of the battery are extended by stabilizing the SEI film and improving the lithium ion transmission rate.
Smart Images

Figure CN119812248A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode material with high specific energy and long cycle life and a preparation method thereof, belonging to the field of lithium ion battery electrode materials. Background Art
[0002] Silicon-carbon materials, as negative electrodes for lithium-ion batteries, have the advantages of high gram capacity, abundant reserves and low cost, and have become the focus and hotspot of current research and development of electrode materials for lithium-ion batteries. However, silicon materials expand in volume during the charging and discharging process, exposing more and more fresh surfaces, which leads to the continuous growth of the solid electrolyte membrane (SEI). The continuous growth of SEI continuously consumes Li from the positive electrode, which leads to the capacity decay of the entire battery.
[0003] In order to provide lithium ions consumed in forming the initial SEI film during formation and repairing the SEI film during cycling, pre-embedded lithium provides additional or supplementary Li to achieve higher efficiency and capacity of the battery. The lithiation of the negative electrode active material substrate includes physical methods and electrochemical methods. The physical method includes depositing a lithium coating on the surface of the negative electrode active material substrate such as silicon particles, thermally induced diffusion of lithium into the substrate such as silicon particles, or spraying stabilized Li powder on the negative electrode belt. The electrochemical method includes using silicon particles and lithium metal plates as electrodes, applying an electrochemical potential to embed Li+ ions into the bulk of the silicon particles. Alternative electrochemical methods include assembling a half-cell using silicon particles and Li metal film electrodes, charging the half-cell, and disassembling the half-cell to obtain lithiated silicon particles. CN108520978B invention embeds a certain amount of lithium into the silicon-carbon negative electrode sheet before making the battery to eliminate the irreversible capacity loss caused by the first embedding of lithium ions into the negative electrode to form an SEI film. The negative electrode pre-lithiation process is complicated. Since metallic Li and its oxides are relatively active in the air, from a safety perspective, it places high demands on the workshop and increases the cost of battery production.
[0004] CN107528048B invented an in-situ pre-embedded lithium method. The source of lithium for pre-embedded lithium comes from the positive electrode. In the initial formation cycle, an additional amount of lithium is extracted from the positive electrode by increasing the cut-off voltage of the full battery; by controlling the discharge capacity, the additional lithium extracted from the positive electrode is stored in the negative electrode, which is ensured in subsequent cycles by keeping the upper cut-off voltage the same as in the initial cycle. When an additional amount of lithium is extracted from the positive electrode, as the amount of lithium removal increases, the positive electrode material will undergo a crystalline phase transition, which will lead to stress accumulation and even irreversible phase transition, which will directly affect the stability of the positive electrode structure, thereby reducing the battery capacity and cycle stability. The positive electrode material of the invention of CN108269972B includes a particle core with gradient Mn doping and a Li2MnO3 coating layer. At the end of high-voltage charging, due to the escape of lattice oxygen, a large number of oxygen vacancies are left on the surface of Li2MnO3. The Mn element in the surface layer becomes unstable due to the reduction of the oxygen coordination number. During multiple charge and discharge processes, the surface gradually transforms into a spinel-like structure. This spinel structure is further transformed into a disordered rock salt structure as the long cycle proceeds. At the same time, under the action of HF in the electrolyte, Mn dissolves into the electrolyte, resulting in a continuous decrease in the discharge voltage, thereby reducing the cycle capacity. Summary of the invention
[0005] The purpose of the present invention is to propose a lithium cobalt oxide positive electrode material matching a silicon-carbon negative electrode and a preparation method thereof. The positive electrode material releases irreversible lithium ions during the first charge and embeds them into the silicon-carbon negative electrode to form an initial SEI film. During multiple cycles of charging, the lithium ions are continuously released and embedded into the negative electrode surface to repair the SEI film, thereby achieving high energy and long cycle life.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a lithium cobalt oxide positive electrode material matching a silicon-carbon negative electrode, which is nano xLi2Mn 1- z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Coated lithium cobalt oxide positive electrode material, wherein 0<x<1.0, 0<y<0.1, 0<z<0.1, a+z=1, 3≤b≤4, M 1 =At least one of Zr, Ti, Si, Nb, Fe, and Mn.
[0008] In a second aspect, the present invention provides a method for preparing a lithium cobalt oxide positive electrode material matching a silicon-carbon negative electrode, the steps comprising:
[0009] 1) Wet mixing is first performed, followed by nano-grinding and calcination to obtain nano-xLi2Mn1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b ; or first solid phase mixing, and then calcination to obtain xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b , and then through nano-milling of xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Nano-xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b ;
[0010] 2) The above nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Lithium cobalt oxide is wet coated and nano xLi2Mn is obtained by low temperature calcination. 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Coated lithium cobalt oxide positive electrode material.
[0011] Further, step 1) comprises: weighing lithium hydroxide, manganese carbonate, M 1The carbonate is poured into a grinder, and grinding balls and ethanol are added, and the mixture is mixed on the grinder for a period of time; the slurry is then transferred to a nano mill, and after grinding for a period of time, it is dried on a dryer for a period of time; the mixed material is calcined in a muffle furnace in oxygen; the calcined material blocks are crushed and sieved to obtain nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b .
[0012] Further, step 2) comprises: weighing lithium cobalt oxide, nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b , poured into a basket grinder, added ethanol, mixed for a period of time, and dried on a rake dryer for a period of time; the mixed material was calcined in an air muffle furnace, and the calcined material blocks were crushed and sieved to obtain coated nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b of lithium cobalt oxide.
[0013] In a third aspect, the present invention provides another method for preparing a lithium cobalt oxide positive electrode material matching a silicon-carbon negative electrode, the steps of which include:
[0014] 1) Liquid phase direct synthesis of nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b , get nano xLi2Mn 1- z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Suspension;
[0015] 2) Disperse lithium cobalt oxide in nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b The suspension is dried to remove the dispersant and calcined at low temperature to obtain nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Coated lithium cobalt oxide positive electrode material.
[0016] Further, step 1) comprises: lithium hydroxide, manganese carbonate, M 1 The carbonate is dissolved in citric acid solution for reaction, and then phosphoric acid solution and ammonia water are added to control the pH to 7, and the reaction is carried out in a high-pressure reactor, and then filtered and washed, and the filter cake is transferred to a nano mill, ethanol is added, and nano xLi2Mn is obtained after grinding for a period of time. 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Suspension.
[0017] Further, step 2) comprises: weighing lithium cobalt oxide and dispersing it in nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b The suspension was poured into a disperser, ethanol was added, mixed for a period of time, and then dried on a dryer for a period of time; the mixed material was calcined in an air muffle furnace, and the calcined material blocks were crushed and sieved to obtain coated nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b of lithium cobalt oxide.
[0018] The advantages and beneficial effects of the present invention are as follows:
[0019] 1. The outermost coating layer of positive electrode material lithium cobalt oxide is 0-20nm xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b .Li2Mn 1-z M 1 z O (3-y) F y A charging platform will appear at around 4.50V, and this electrochemical reaction is irreversible. During the first charge, the Li2Mn 1-z M 1 z O (3-y) F y The Li released from the electrolyte is embedded in the surface of the silicon-carbon anode to form a SEI film. 1-z M z O (3-y) F y Mn formed after the first delithiation 1-z M z O 2-y F y With Li2M 1 a O b Formation of solid solution Li2Mn 1-z M 1 z+a O b-y F y , which has a deintercalation capacity of 2 lithium ions, realizes multi-electron exchange reaction, continuously provides Li ions in subsequent multiple cycles of charging, and continuously repairs the surface SEI film rupture caused by the expansion of the silicon-carbon negative electrode. The 0-20nm lithium-containing coating layer on the outermost surface of the positive electrode material lithium cobalt oxide provides sufficient lithium ions for the formation of a stable SEI film on the silicon-carbon negative electrode side. Because it has the same layered structure as the main body lithium cobalt oxide, it is conducive to the deintercalation of lithium ions during the charging and discharging process, and improves the lithium ion transmission rate during the charging and discharging process. At the same time, there is no loss of lithium in the positive electrode material lithium cobalt oxide, thereby improving the cycle capacity and life.
[0020] 2. At the end of high voltage charging (≥4.50v), due to the release of lattice oxygen, a large number of oxygen vacancies are left on the surface of Li2MnO3. The Mn element on the surface becomes unstable due to the reduction of oxygen coordination number. During multiple charge and discharge processes, the surface gradually transforms into a spinel-like structure. This spinel structure further transforms into a disordered rock salt structure with long cycles, resulting in a continuous decrease in discharge voltage and thus a reduction in cycle capacity. The solid solution Li2Mn formed during the charging process 1-z M 1z+a O b-y F y M in the transition layer 1 Occupies the Mn site to stabilize the layered structure, and F occupies the oxygen site to inhibit the escape of lattice oxygen. 1 The synergistic effect with F greatly inhibits the transformation of the surface Li2MnO3 layered structure to the spinel structure and disordered rock salt structure, while reducing the dissolution of Mn in the electrolyte and improving the stability of the surface Li2MnO3 layered structure during the cycle, thereby improving the battery capacity and cycle stability.
[0021] 3. The outermost surface of the positive electrode material lithium cobalt oxide is coated with xLi2Mn with 0-20nm 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b During the high temperature sintering coating process, part of the Mn 4+ 、M 1 、F - Diffused to the surface of lithium cobalt oxide to form surface doped Mn 4+ 、M 1 、F - Transition layer of lithium cobalt oxide, Mn 4+ Occupies the Co position in the Co-O octahedron and does not participate in the redox reaction during charge and discharge (≥4.50v), M 1 Occupies the Co position in the Co-O octahedron, Mn 4+ With M 1 The stability of the Co-O octahedral structure on the surface of lithium cobalt oxide in the high-lithiation state is improved. - It occupies oxygen sites and inhibits the escape of lattice oxygen on the surface of lithium cobalt oxide, thereby improving the stability of the Li-O octahedral structure on the surface of lithium cobalt oxide under high delithiation state, thereby improving the battery capacity and cycle stability.
[0022] 4. The present invention has low process cost and is easy to mass produce. By matching it with a silicon-carbon negative electrode, the capacity and life of the lithium-ion battery are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the surface Li distribution curve in Example 2.
[0024] Figure 2 This is the surface Mn distribution curve in Example 2.
[0025] Figure 3 This is the surface Ti distribution curve in Example 2.
[0026] Figure 4 This is the surface F distribution curve in Example 2.
[0027] Figure 5 This is a TEM image of the lithium cobalt oxide prepared in Example 2. DETAILED DESCRIPTION
[0028] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.
[0029] Example 1: 5nm thickness 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr 0.98 O3 coated lithium cobalt oxide
[0030] 1) Nano 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr 0.98 O3 preparation:
[0031] According to 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr 0.98 The chemical formula molar ratio of lithium hydroxide, manganese carbonate, zirconium oxide and lithium fluoride was weighed, poured into a grinder, and grinding balls and ethanol were added. The mixture was mixed on the grinder for a certain time. The slurry was then transferred to a nano mill, ground for a certain time, and dried on a dryer for a certain time. The mixed materials were calcined in a muffle furnace in an oxidizing gas of oxygen. The calcined material blocks were crushed and sieved to obtain nano 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr 0.98 O3.
[0032] 2) Nano 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr 0.98 Preparation of O3-coated lithium cobalt oxide:
[0033] Weighing lithium cobalt oxide and nano 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr0.98 O3, nano 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr 0.98 O3 accounts for 0.008% of the mass of lithium cobalt oxide, poured into a basket grinder, added ethanol, solid-liquid ratio 1:2, mixed for 1 hour, dried on a rake dryer for 2 hours. The mixed material was calcined at 500℃ in an air muffle furnace and kept warm for 3 hours. The calcined material blocks were crushed and passed through a 300 mesh sieve to obtain coated nano 0.2Li2Mn 0.98 Zr 0.02 O 2.98 F 0.02 0.8Li2Zr 0.98 O3 lithium cobalt oxide.
[0034] Example 2: 10nm thickness 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 O3 coated lithium cobalt oxide
[0035] 1) Nano 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 O3 preparation:
[0036] According to 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 The chemical formula molar ratio of lithium hydroxide, manganese carbonate, titanium oxide and lithium fluoride was weighed, poured into a grinder, and grinding balls and ethanol were added. The mixture was mixed on the grinder for a certain time. The slurry was then transferred to a nano mill, ground for a certain time, and dried on a dryer for a certain time. The mixed materials were calcined in a muffle furnace in an oxidizing gas of oxygen. The calcined material blocks were crushed and sieved to obtain nano 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 O3.
[0037] 2) Nano 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96Preparation of O3-coated lithium cobalt oxide:
[0038] Weighing lithium cobalt oxide and nano 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 O3, nano 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 O3 accounts for 0.008% of the mass of lithium cobalt oxide, poured into a basket grinder, added ethanol, solid-liquid ratio 1:2, mixed for 1 hour, dried on a rake dryer for 2 hours. The mixed material was calcined at 500℃ in an air muffle furnace and kept warm for 3 hours. The calcined material blocks were crushed and passed through a 300 mesh sieve to obtain coated nano 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 O3 lithium cobalt oxide.
[0039] Example 3: 15nm thickness 0.6Li2Mn 0.94 Si 0.06 O 2.94 F 0.06 0.4Li2Si 0.94 O3 coated lithium cobalt oxide
[0040] 1) Nano 0.6Li2Mn 0.94 Si 0.06 O 2.94 F 0.06 0.4Li2Si 0.94 O3 preparation:
[0041] According to 0.6Li2Mn 0.94 Si 0.06 O 2.94 F 0.06 0.4Li2Si 0.94 The chemical formula molar ratio of lithium hydroxide, manganese carbonate, nano silicon dioxide and lithium fluoride were weighed, poured into a grinder, and grinding balls and ethanol were added. The mixture was mixed on the grinder for a certain time. The slurry was then transferred to a nano mill, ground for a certain time, and dried on a dryer for a certain time. The mixed materials were calcined in a muffle furnace in an oxidizing gas of oxygen. The calcined material blocks were crushed and sieved to obtain nano 0.6Li2Mn 0.94 Si 0.06 O 2.94 F 0.06 0.4Li2Si 0.94O3.
[0042] 2) Nano 0.6Li2Mn 0.94 Si 0.06 O 2.94 F 0.06 0.4Li2Si 0.94 Preparation of O3-coated lithium cobalt oxide:
[0043] Weighing lithium cobalt oxide and nano 0.4Li2Mn 0.96 Ti 0.04 O 2.96 F 0.04 0.6Li2Ti 0.96 O3, nano 0.6Li2Mn 0.94 Si 0.06 O 2.94 F 0.06 0.4Li2Si 0.94 O3 accounts for 0.008% of the mass of lithium cobalt oxide, poured into a basket grinder, added ethanol, solid-liquid ratio 1:2, mixed for 1 hour, dried on a rake dryer for 2 hours. The mixed material was calcined at 500℃ in an air muffle furnace and kept warm for 3 hours. The calcined material blocks were crushed and passed through a 300 mesh sieve to obtain coated nano 0.6Li2Mn 0.94 Si 0.06 O 2.94 F 0.06 0.4Li2Si 0.94 O3 lithium cobalt oxide.
[0044] Example 4: 20nm thickness 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92 O4 coated lithium cobalt oxide
[0045] 1) Nano 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92 O4 preparation:
[0046] According to 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92O4, weigh lithium hydroxide, manganese carbonate, niobium pentoxide, and lithium fluoride, pour them into a grinder, add grinding balls and ethanol, and mix them on the grinder for a certain time; then transfer the slurry to a nano mill, grind for a certain time, and dry it on a dryer for a certain time; the mixed materials are calcined in an oxidizing gas oxygen in a muffle furnace; the calcined material blocks are crushed and sieved to obtain nano 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92 O4.
[0047] 2) Nano 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92 Preparation of O4-coated lithium cobalt oxide:
[0048] Weighing lithium cobalt oxide and nano 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92 O4, nano 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92 O4 accounts for 0.008% of the mass of lithium cobalt oxide, poured into a basket grinder, added ethanol, solid-liquid ratio 1:2, mixed for 1 hour, dried on a rake dryer for 2 hours. The mixed material was calcined at 500℃ in an air muffle furnace and kept warm for 3 hours. The calcined material blocks were crushed and passed through a 300 mesh sieve to obtain coated nano 0.8Li2Mn 0.92 Nb 0.08 O 2.92 F 0.08 0.2Li3Nb 0.92 O4 of lithium cobalt oxide.
[0049] Example 5: 20nm thickness 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 SiO4 coated lithium cobalt oxide
[0050] 1) Nano 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.080.2Li2Fe 0.5 Mn 0.5 SiO4 preparation:
[0051] According to 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 The chemical formula molar ratio of SiO4 was calculated by weighing lithium hydroxide, manganese carbonate, ferrous sulfate and lithium acetate, dissolving them in 0.1mol / L citric acid + hydrofluoric acid solution, reacting at 80℃ for 3 hours, adding phosphoric acid and ammonia water, controlling the pH to 7, reacting at 300℃ for 4 hours in a high pressure reactor, then filtering and washing to obtain 20 nanometers 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 SiO4 suspension.
[0052] 2) Nano 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 Preparation of SiO4 coated lithium cobalt oxide:
[0053] Nano 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 Preparation of SiO4-coated lithium cobalt oxide: weighing lithium cobalt oxide, nano 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 SiO4 accounts for 0.008% of the mass of lithium cobalt oxide, and lithium cobalt oxide is dispersed into medium-nano 0.8Li2Mn 0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 SiO4 suspension, stirred for 2 hours, filtered and dried. After drying, the material was calcined in a muffle furnace at 600℃ and kept warm for 3 hours. The calcined material blocks were crushed and passed through a 300 mesh sieve to obtain coated nano 0.8Li2Mn0.95 Fe 0.05 O 2.92 F 0.08 0.2Li2Fe 0.5 Mn 0.5 Lithium cobalt oxide of SiO4.
[0054] Comparative Example 1: Lithium Cobalt Oxide LiCo 0.09 Al 0.01 O2, this is the common Al2O3, TiO2 coated lithium cobalt oxide, TiO2 accounts for 0.005% of the mass of lithium cobalt oxide.
[0055] Comparative Example 5: Li2Mn 0.95 Fe 0.05 O3 coated lithium cobalt oxide.
[0056] Product performance test:
[0057] XPS etching results:
[0058] XPS etches the surface Li, Mn, Ti, and F contents from 0 to 40 nm, and obtains an XPS spectrum every 10 nm of etching depth.
[0059] Surface 0-20nmLi + 、Ti 4+ 、F - The peak area is significantly higher than 20-40 nm, indicating that Li + 、Ti 4+ 、F - It is mainly distributed in the range of 0 to 20 nm on the surface, achieving a surface coating of 0-20 nm.
[0060] Mn 4+ The surface is evenly distributed at 0-40nm, indicating that Mn diffusion and co-dissolution occurred during the sintering process, that is, the surface coating of 0-20nm was achieved, and doped Mn was formed at 20-40nm. 4+ The Mn2p binding energy at 20-40nm depth is significantly higher than that at 0-20nm, which further indicates that the valence state of 20-40nm Mn is higher than that of 0-20nm Mn. During deep charge and discharge (≥4.50v), Mn 4+ It does not participate in the electrochemical redox reaction, but plays a role in stabilizing the Co-O octahedron in the high delithiation state of lithium cobalt oxide (≥4.50v), thereby improving the cycle stability.
[0061] TEM results:
[0062] TEM images show that the surface 0-20nm is a layered structure, which further shows that the surface is coated with 0.4Li2Mn 0.96 Ti 0.04 O2.96 F 0.04 0.6Li2Ti 0.96 O3 and the main lithium cobalt oxide both have layered structures and do not have different crystal phases, which is conducive to lithium ion transmission and improves the lithium ion diffusion coefficient, thereby reducing polarization during charging and discharging, reducing battery impedance, and improving cycle capacity and life.
[0063] The present invention is mainly used in high energy density lithium ion batteries, and its performance can meet the following requirements: the capacity retention rate is more than 80% after 800 cycles at 45°C, the thickness expansion is less than 8% after 30 days of storage at 60°C, and the thickness expansion is less than 8% after 8 hours of storage at 85°C.
[0064] Table 1 Lithium ion diffusion coefficient of positive electrode materials
[0065] Operating voltage Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 3.0~4.55v 6.8E-9 3.1E-8 5.1E-8 7.1E-8 8.7E-8 4.8E-10 5.1E-9
[0066] Table 2 Initial impedance of battery in Example 2
[0067]
[0068] Table 3 2Ah 3.0-4.55V battery capacity, capacity retention rate and charge transfer impedance
[0069]
[0070] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A lithium cobalt oxide positive electrode material matching a silicon-carbon negative electrode, characterized in that: Nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Coated lithium cobalt oxide positive electrode material, wherein 0<x<1.0, 0<y<0.1, 0<z<0.1, a+z=1, 3≤b≤4, M 1 =At least one of Zr, Ti, Si, Nb, Fe, and Mn.
2. A method for preparing a lithium cobalt oxide positive electrode material matching a silicon-carbon negative electrode according to claim 1, characterized in that the steps include: 1) Wet mixing is first performed, followed by nano-grinding and calcination to obtain nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b ; or first solid phase mixing, and then calcination to obtain xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b , and then through nano-milling of xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Nano-xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b ; 2) The above nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Lithium cobalt oxide is wet coated and nano xLi2Mn is obtained by low temperature calcination. 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Coated lithium cobalt oxide positive electrode material.
3. The preparation method according to claim 2, characterized in that: Step 1) comprises: weighing lithium hydroxide, manganese carbonate, M 1 The carbonate is poured into a grinder, and grinding balls and ethanol are added, and the mixture is mixed on the grinder for a period of time; the slurry is then transferred to a nano mill, and after grinding for a period of time, it is dried on a dryer for a period of time; the mixed material is calcined in a muffle furnace in oxygen; the calcined material blocks are crushed and sieved to obtain nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b .
4. The preparation method according to claim 2, characterized in that: Step 2) includes: weighing lithium cobalt oxide, nano xLi2Mn 1- z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b , poured into a basket grinder, added ethanol, mixed for a period of time, and dried on a rake dryer for a period of time; the mixed material was calcined in an air muffle furnace, and the calcined material blocks were crushed and sieved to obtain coated nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b of lithium cobalt oxide.
5. A method for preparing a lithium cobalt oxide positive electrode material matching a silicon-carbon negative electrode according to claim 1, characterized in that the steps include: 1) Liquid phase direct synthesis of nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b , get nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Suspension; 2) Disperse lithium cobalt oxide in nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b The suspension is dried to remove the dispersant and calcined at low temperature to obtain nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Coated lithium cobalt oxide positive electrode material.
6. The preparation method according to claim 5, characterized in that: Step 1) comprises: lithium hydroxide, manganese carbonate, M 1 The carbonate is dissolved in citric acid solution for reaction, and then phosphoric acid solution and ammonia water are added to control the pH to 7, and the reaction is carried out in a high-pressure reactor, and then filtered and washed, and the filter cake is transferred to a nano mill, ethanol is added, and nano xLi2Mn is obtained after grinding for a period of time. 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b Suspension.
7. The preparation method according to claim 5, characterized in that: Step 2) comprises: weighing lithium cobalt oxide and dispersing it in nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b The suspension was poured into a disperser, ethanol was added, mixed for a period of time, and then dried on a dryer for a period of time; the mixed material was calcined in an air muffle furnace, and the calcined material blocks were crushed and sieved to obtain coated nano xLi2Mn 1-z M 1 z O (3-y) F y ·(1-x)Li2M 1 a O b of lithium cobalt oxide.
Citation Information
Patent Citations
Silicon-carbon composite, method for preparing the composite, electrode material containing the composite, and battery
CN107528048B
A novel high-voltage lithium cobalt oxide cathode material and its preparation method
CN108269972B
A lithium-ion battery lithium replenishment process
CN108520978B